Teen library events : a month-by-month guide - Edwards, Kirsten, 1965- (Greenwood professional guides for young adult librarians., 2002)
This is a guide for young adult librarians who wish to create inexpensive, time-saving young adult library programmes. For each month in the calendar year, two or three programmes are presented with instructions, sample flyers, letters and lists.